Model for end stage of liver disease (MELD) is better than the Child-Pugh score for predicting in-hospital mortality related to esophageal variceal bleeding - Flores Rendón, Ángel Ricardo; González González, José Alberto; García Compeán, Diego; Maldonado Garza, Héctor Jesús; Garza Galindo, Aldo Azael (2008)
Aim: The Child Pugh and MELD are good methods for predicting mortality in patients with chronic liver disease. We investigated their performance as risk factors for failure to control bleeding, in-hospital overall mortality and death related to esophageal variceal bleeding episodes. Methods: From a previous collected database, 212 cirrhotic patients with variceal bleeding admitted to our hospital were studied. The predictive capability of Child Pugh and MELD scores were compared using c statistics. Results: The Child-Pugh and MELD scores showed marginal capability for predicting failure to control bleeding (the area under receiver operating characteristics curve (AUROC) values were 0.05). The AU-ROC value of MELD for predicting mortality related to variceal bleeding was higher than the Child-Pugh score: 0.905 (CI 95% 0.801-1.00) vs 0.794 (CI 95% 0.676 - 0.913) respectively (p < 0.05). Conclusions: MELD and Child-Pugh were not efficacious scores for predicting failure to control bleeding. The Child-Pugh and MELD scores had similar capability for predicting in-hospital overall mortality. Nevertheless, MELD was significantly better than Child-Pugh score for predicting in-hospital mortality related to variceal bleeding.